Electroosmotic flow velocity measurements in a square microchannel - Hsieh, Shou-Shing (Springer-Verlag, 2006)
Experiments were performed using a microparticle image velocimetry (MPIV) for 2D velocity distributions of electroosmotically driven flows in a 40-mm-long microchannel with a square cross section of 200×200 μm. Electroosmotic flow (EOF) bulk fluid velocity measurements were made in a range of streamwise electric field strengths from 5 to 25 kV/m. A series of seed particle calibration tests can be made in a 200×120×24,000-μm untreated polydimethyl siloxane (PDMS channel incorporating MPIV to determine the electrophoretic mobilities in aqueous buffer solutions of 1× TAE, 1× TBE, 10 mM NaCl, and 10 mM borate. A linear/nonlinear (due to Joule heating) flow rate increase with applied field was obtained and compared with those of previous studies. A parametric study, with extensive measurements, was performed with different electric field strength and buffer solution concentration under a constant zeta potential at wall for each buffer. The characteristics of EOF in square microchannels were thus investigated. Finally, a composite correlation of the relevant parameters was developed in the form of [Formula: see text] within ±1% accuracy for 99% of the experimental data.